Barriers and drivers for solar dryer adoption in Bhutan and Nepal : A study from the perspective of farmers and producers - Andreasson, Noah; Lundevaller, Linda; Sonesson, Ida; Lundquist, Magnus; Dorji, Cheku; Humagai, Bharat Kumar; Zangmo, Phurpa; Baral, Bivek; Davidsson, Henrik; Andersson, Martin ; 0000-0001-5057-4908 (Energy for Sustainable Development, 2026)
Post-harvest losses are a significant challenge in Bhutan and Nepal, where around half and two thirds of the population rely on agriculture for their livelihoods. Traditional open-sun drying methods suffer from contamination, slow drying and weather vulnerability, contributing to losses that can reach 40%–73% for certain crops. While improved solar drying technology offers promising opportunities to reduce such losses, adoption among small-scale farmers remains limited, despite clear benefits and abundant solar resources in both countries. Empirical studies investigating the dynamics behind this reality are also scarce in the region. This study aims to address this knowledge gap, by investigating barriers and drivers influencing solar dryer adoption among small-scale farmers in Bhutan and Nepal using thematic analysis. It is based on 67 semi-structured interviews with local farmers and carpenters across six regions, supplemented by literature reviews and interviews with ministries and agricultural authorities. 24 distinct barriers and 28 drivers are identified, spanning economic, technical, governmental and design-related factors, among others. Lack of awareness emerged as the primary barrier in both countries: 59% and 64% of non-users in Bhutan (n = 19 of 32) and Nepal (n = 18 of 28) respectively were completely unaware that solar dryers exist, and 82%–95% of those who elaborated (n = 23 of 28 and n = 19 of 20 for Bhutan and Nepal respectively) cited insufficient information as the primary reason for not having invested in improved solar drying technology. Other critical barriers include concerns about long-term technical support reinforced by negative experiences with previously failed pilot projects, challenging investment costs compounded by low subsidy awareness, inadequate market infrastructure for dried products, as well as design limitations particularly regarding capacity, portability, and monsoon-season functionality. The findings reveal deep interconnections between barriers, indicating that isolated interventions risk ineffectiveness. Region-specific design adaptations, robust technical support networks, as well as strategic campaigns to spread both awareness and information about the technology and the available governmental support mechanisms, emerged as essential for successful technology diffusion.
Publisher Copyright: © 2026 The Authors
Keywords: Barriers and drivers; Post-harvest losses; Rural development; Solar dryer; Solar drying; Technology adoption